Breeding and Ontogeny of the Aquarium-Traded Scissortail Rasbora (Rasbora trilineata) - Krittima Kasamawut; Suriya Udduang; Supalug Kattakdad; Kasama Danwandee; Achara Jutagate; Samnao Saowakoon; Tuantong Jutagate (Animals)
Fishes of the genus Rasbora in the Cyprinidae family comprise 88 species [...]